2019
DOI: 10.1139/cjpp-2019-0078
|View full text |Cite
|
Sign up to set email alerts
|

Is the cardioprotective effect of the ACE2 activator diminazene aceturate more potent than the ACE inhibitor enalapril on acute myocardial infarction in rats?

Abstract: Myocardial infarction is a major cause of cardiac dysfunction. All components of the cardiac renin–angiotensin system (RAS) are upregulated in myocardial infarction. Angiotensin-converting enzyme (ACE) and ACE2 are key enzymes involved in synthesis of components of RAS and provide a counter-regulatory mechanism within RAS. We compared the cardioprotective effect of the ACE2 activator diminazene aceturate (DIZE) versus the ACE inhibitor enalapril on post acute myocardial infarction (AMI) ventricular dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…This study also revealed increased Ang-(1–7), ACE2, and MasR, and decreased ACE and AT1R expression in the myocardium. Another study reported that the administration of DIZE for four weeks could significantly increase myocardial ACE2 protein concentration after the myocardial infarction, as well as improve cardiac function by preserving carotid flow, stroke volume, and cardiac output [ 20 ]. Taken together, these data support the role of DIZE in improving the function of Ang-(1–7)/MasR by activating ACE2 and elevating cardiac ACE2 protein to play a protective role in the pathogenesis of cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also revealed increased Ang-(1–7), ACE2, and MasR, and decreased ACE and AT1R expression in the myocardium. Another study reported that the administration of DIZE for four weeks could significantly increase myocardial ACE2 protein concentration after the myocardial infarction, as well as improve cardiac function by preserving carotid flow, stroke volume, and cardiac output [ 20 ]. Taken together, these data support the role of DIZE in improving the function of Ang-(1–7)/MasR by activating ACE2 and elevating cardiac ACE2 protein to play a protective role in the pathogenesis of cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown DIZE to have an antihypertensive effect, similar to that of ACE inhibitors [27,28]. In models of acute myocardial infarction and chronic heart failure, the administration of DIZE could reduce the size of the myocardial infarction and improve ventricular systolic and diastolic function, as well as inhibit myocardial fibrosis [14,20,24,[29][30][31]. The underlying protective mechanism of DIZE on the cardiovascular system is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of ex vivo hearts by administration of 10 −8 M Ang(1-7) into the bath solution using Langendorff technique re-established the impulse conduction during ischemia-reperfusion and reduced incidence of arrhythmias during IR, possibly due to cardiomyocyte hyperpolarization via the activation of sodium pump [ 89 ]. Activation of ACE2 by diminazene aceturate (DIZE) treatment [ 86 , 90 , 91 , 92 ] led to an improvement of almost all evaluated parameters (however, lacking evidence against amelioration of hypertrophy). These effects were abolished by ACE2 inhibition (“compound 16”) [ 84 , 86 ] or by Mas-receptor antagonist (A779) [ 24 , 88 ].…”
Section: Ace2 Deficiency-related Pathologies Underlying Hypoxiamentioning
confidence: 99%
“…12 Moreover, Entresto can also effectively inhibit the proliferation of vascular endothelial cells, smooth muscle cells and cardiomyocytes and suppress the aldosterone secretion, therefore alleviating the ventricular remodeling in AMI patients. [13][14][15][16][17] NT-proBNP is a long amino acid peptide chain secreted in case of heart failure, and it has been employed for the diagnosis of heart failure. 18 The significant increase or decrease of serum NT-proBNP level also predicts the elevated risk of sudden death and hospitalization.…”
mentioning
confidence: 99%